2016
DOI: 10.2139/ssrn.2747856
|View full text |Cite
|
Sign up to set email alerts
|

Gender Differences in Climate Change Perceptions and Adaptation Strategies: An Intra-Household Analysis from Rural Kenya

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…For example, young, poor women who were household heads were the least likely to adopt drought-tolerant maize in Uganda, whereas spouses of male household heads influenced adoption decisions on their husbands' fields 9 . Only a few studies paid attention to intra-household dynamics, gender roles and relations, and how these shape adaptation decisions 9,28 . This limited attention on intra-household gender dynamics and decision making around climate-resilient seed adoption skews the conclusions and recommendations, as the literature does not equally represent the challenges and views of women.…”
Section: Discussionmentioning
confidence: 99%
“…For example, young, poor women who were household heads were the least likely to adopt drought-tolerant maize in Uganda, whereas spouses of male household heads influenced adoption decisions on their husbands' fields 9 . Only a few studies paid attention to intra-household dynamics, gender roles and relations, and how these shape adaptation decisions 9,28 . This limited attention on intra-household gender dynamics and decision making around climate-resilient seed adoption skews the conclusions and recommendations, as the literature does not equally represent the challenges and views of women.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, other capacity building initiatives have been claimed to be successful in filling these gaps. For instance, demand-driven extension services (Ngigi et al, 2016) and farmer-to-farmer training approaches (Lukuyu et al, 2012). Strengthening human capacity is a precondition for improving the sustainability of rural livelihoods for communities that depend on rainfed agriculture as was found for example in Azerbaijan (Aliloo & Dashti, 2021).…”
Section: Capacity Developmentmentioning
confidence: 99%
“…There is a need to provide sound loan products to finance agriculture by removing barriers to both lenders and borrowers. One way, especially for asset-poor farmers, is through group-based access (Ngigi et al, 2016). Furthermore, collective action has been put forward as a strategy to improve farmers' involvement in agricultural value chains Fig.…”
Section: Farm Enterprisesmentioning
confidence: 99%
“…Studies on smallholders' responses to climate stress in Kenya, Uganda, Ghana and Bangladesh, by Jost et al (2016); Ngigi et al (2016;Chamberlin et al (2015) and Ng'ang'a et al (2017) suggested that livelihood diversification as a successful household adaptation strategy can undermine the interest and status of the married women within homesteads. Economic pressure has however forced women to change from their traditional roles as housewives to engagement in off-farm wage earning activities.…”
Section: Introductionmentioning
confidence: 99%